2014
DOI: 10.1073/pnas.1406763111
|View full text |Cite|
|
Sign up to set email alerts
|

Contrasted coevolutionary dynamics between a bacterial pathogen and its bacteriophages

Abstract: Significance Scientists have long debated the dynamic form of perpetual reciprocal adaptations, or coevolution, between hosts and their parasites. The two main types of antagonistic coevolution described to date are arms race dynamics, in which interaction traits escalate through time, and fluctuating selection dynamics, in which traits cycle through time. We used experimental evolution between Pseudomonas aeruginosa and a panel of its lytic phages and found the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 68 publications
7
106
0
Order By: Relevance
“…Studies performed in chemostats have addressed the coevolution dynamics of phage and bacteria in controlled growth conditions (Betts et al, 2014;Buckling & Rainey, 2002). Two possible outcomes were described in some assays where prey and predators are left to evolve for a long time.…”
Section: Red Queen Dynamics/arms Race Coevolutionmentioning
confidence: 99%
“…Studies performed in chemostats have addressed the coevolution dynamics of phage and bacteria in controlled growth conditions (Betts et al, 2014;Buckling & Rainey, 2002). Two possible outcomes were described in some assays where prey and predators are left to evolve for a long time.…”
Section: Red Queen Dynamics/arms Race Coevolutionmentioning
confidence: 99%
“…For example, co‐evolutionary dynamics can follow either an arms race or fluctuating selection dynamics depending on the interacting parasite species (Betts, Kaltz, & Hochberg, 2014), while considerable variation exists in host species sensitivity to a one given parasite species (Thompson, 2005). This is especially true with bacteria, where small differences between different genotypes can have large effects on fitness.…”
Section: Introductionmentioning
confidence: 99%
“…We found that in ironlimited monocultures, producer bacteria were able to recover from phage predation, suggestive of resistance evolution [48], rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: Discussionmentioning
confidence: 78%